The Nutritional Content of Egg and Blood’s Lipid Profile of Layer Fed by Kepok Banana Meal (Musa paradisiaca L.) as Feed Supplement - Jein Rinny Leke; Erwin Wantasen; Ratna Siahaan; Florencia Sompie (ANIMAL PRODUCTION, 2022)
This study was aimed to evaluate the nutritional of content of egg and the fat profile of layers by feeding of kepok Banana flour (Musa paradisiaca formantypica) as feed supplement. A total of 200 laying 58-week-old hens were used in the study, with 5 treatments and 5 replications, each of which was filled with 8 chickens. The treatments were applied in a completely randomized design, continued with Duncan’s test. The treatments given by kepok banana flour were 0%, 5%, 10%, 15% and 20% substitution of corn flour. This research was conducted for 8 weeks. The parameters measure included egg crude protein (%), egg crude fat (%), egg white crude protein (%), egg yellow fat (%), egg cholesterol (mg/100 g), blood cholesterol (mg/dl), blood LDL cholesterol (mg/dl), and blood HDL cholesterol (mg/dl) of the laying hens. The results showed that the utilization of kepok banana flour up to 20% substitution of yellow corn had a highly significant effect on egg protein content, egg white protein, egg fat content, egg cholesterol content, chicken blood cholesterol, chicken blood HDL, chicken blood LDL and triglycerides of chicken blood. It was concluded that kepok banana flour substitution of up to 20% as a feed source can increase the nutritional content of chicken eggs and the fat profile of laying hens.